PREGNANCY MONITORING IN PATIENTS WITH EXCESS WEIGHT OR OBESITY - E. L. Borovkova (IRBIS LLC, 2016)
It is known that pregnancy monitoring in patients with excess weight or obesity is associated with many problems due to increased risk of occurrence of serious obstetric and somatic complications in such patients. The article gives practical recommendations over management of such patients (pregnancy is the only period in life of obese female when she is allowed to gain weight). The medicinal therapy should be administered with care. Reasonable choice of food products allows better control of pregnancy course. The optimal labor time for obese patient is 38 weeks, and the method of delivery is defined according to obstetric indications.